Fatores associados a Traços de alergia no segundo ano de vida: uma análise na Coorte BRISA - MUNIZ, Alessandra Karla Oliveira Amorim Muniz (2023)
Rates of allergic diseases have increased in children and are strongly influenced by risky infections in early life. During this period, unfavorable factors can permanently and irreversibly alter the immune system, increasing the risk of allergic diseases and other non- communicable diseases in the future. There are few studies aimed to investigate factors associated with allergic diseases in children's first two years; and among those existent, include only an allergic disease. This thesis supported the construction of a latent outcome called Allergy Traits, consisting of three allergic diagnoses (allergic rhinitis, atopic dermatitis, and food allergies), to achieve its main objective: to analyze the factors associated with Allergy Traits in the second year of children in the BRISA cohort. For this purpose, Structural Equation Modeling was used, which is an analytical tool that enables the analysis of the latent outcome with reduced measurement error, which enhanced the identification of factors associated with this outcome in the analysis of the two articles of this thesis. The first article Factors associated with Allergy Traits around the 2nd year of life: a Brazilian cohort study, published in BMC Pediatrics, analyzed the pre- and perinatal factors associated with Allergy Traits in the second year of life of children from the birth cohort from Ribeirão Preto, São Paulo, Brazil (n=3644). The following exploratory variables were included: mother's color, socioeconomic status, pre-gestational body mass index, hypertension and gestational diabetes, smoking, gestational age, 5-minute Apgar score, birth weight, type of delivery and family allergy, latent Variable deduced from family histories of allergic rhinitis, atopic dermatitis, and asthma. Better Socioeconomic Status (SC=0.238; p<0.001) and higher values of Family Allergy (SC=1.224; p<0.001) were associated with higher values of Allergy Traits in children. Gestational hypertension was associated with higher values of Allergy Traits in children (SC=0.170; p=0.022) and exclusive breastfeeding was protective for the outcome (SC= - 0.191; p=0.001). In the second article Sugar-Sweetened Beverages and Allergy Traits at Second Year of Life: BRISA Cohort Study, to be submitted to Nutrients, analyzing data from the São Luís prenatal cohort (n=1144), we tested the hypothesis that early exposure to sugar sweetened beverages (SSBs) would increase the risk of allergies in the second year of life. Early exposure to SSBs was analyzed as a percentage of daily calories, based on 24-hour recall data, and included industrialized fruit juices (excluding 100% fruit juices), soft drinks, and ready-to-eat chocolate drinks. Other variables analyzed were: socioeconomic status, age of the child, body mass index z-score for age, episodes of diarrhea, and breastfeeding. The highest percentage of daily calories consumed from SSBs was associated with the highest values of Allergy Traits (SC=0.174; p=0.025). Increasing age (SC=-0.181; p=0.030) reduced the values of Allergy Traits. Episodes of diarrhea correlated with allergic characteristics in children (SC=0.287; p=0.015). Our findings support the investigation of risk factors for allergy to begin in the first stages of life, suggesting the adoption of strategies that impact gestational hypertension, exclusive breastfeeding, and non-exposure to SSBs in early life. The latent variable Allergy Traits proposed in this work was not aimed at clinical implementation in the diagnosis but at the development of epidemiological studies, which, like those developed in this thesis, will be able to identify risk and protection factors with greater consistency and encourage prevention strategies in health care for newborns and children.